ASSESSMENT OF PERIPHERAL INTRAVENOUS CANNULA INSERTION PRACTICE AMONG HEALTH CARE WORKERS OF SULAIMANI SURGICAL TEACHING HOSPITAL, SULAIMANI, IRAQ - Ahmed, Khunaw A.; Hamawandi, Nizar M. T. (Journal of Sulaimani Medical College, 2020)
Background Cannula insertion is done to provide venous access for therapeutic purposes such as administration of fluids, medications, chemotherapy, and blood products. Health care workers involved in the care of intravenous access devices must be competent because the skill level is critical in reducing and preventing complications. Objectives To assess the practice of the health care workers regarding intravenous cannula insertion and to find out the association between practice and socio-demographic characteristics. Methods An observational descriptive study was done in which a sample of health care workers in three operation theatres and 8 surgical wards of Sulaimani surgical teaching hospital during the period of 15th September 2018 up to the end of April 2019. The study sample was chosen by a convenience sample technique. Data were collected by direct interview and observation, through a questionnaire that consists of 9 items, and an observational checklist which consists of three parts with 82 items. Data were analyzed by SPSS (Statistical Package for Social Sciences) version 24. Results The majority of the health care workers were female (66.7%), between age group (41-50) years (56.9%), nursing institute graduate (47.1%), have been employed for more than 21 years (39.2%), equipment preparation and patient preparation practice among health care workers were low (22.7%), health care workers who performed the cannula insertion procedure properly were (34.6%), documentation and post-procedure care for the cannula insertion by the health care workers were (22.7%). The study showed that there were no significant associations between the health care worker’s gender, age, level of education, and years of employment and their practice. Conclusion This study showed a practice deficit in most items of cannula insertion practice regarding the preparation of the equipment and preparation of the patient, cannula insertion procedure, and post-procedure care of waste and documentation. We recommend the arrangement of special training sessions for the health care workers.
Keywords: Assessment; Cannula insertion; Practice; Surgical Teaching Hospital